1997
DOI: 10.1002/(sici)1097-0290(19971105)56:3<279::aid-bit5>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

On-line monitoring and control of methanol concentration in shake-flask cultures ofPichia pastoris

Abstract: The methylotrophic yeast Pichia pastoris can be used to express recombinant genes at high levels under the control of the methanol‐inducible alcohol oxidase 1 (AOX1) promoter. Accurate regulation of the methanol concentration in P. pastoris cultures is necessary to maintain induction, while preventing accumulation of methanol to cytotoxic levels. We developed an inexpensive methanol sensor that uses a gas‐permeable silicone rubber tube immersed in the culture medium and an organic solvent vapor detector. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
1
3

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 16 publications
(16 reference statements)
0
56
1
3
Order By: Relevance
“…Production of large amounts of heterologous proteins in shake-flask culture is difficult, due to the limitations of volume, oxygen transfer, substrate addition and an inability to monitor these factors efficiently. Methods of monitoring methanol in shake flasks are available, such as organic solvent vapour detectors [40], and the oxygen transfer of these systems can be increased by the use of baffles [114]. On-line measurement of oxygen and carbon dioxide transfer rates in shake flasks has also been demonstrated using a respiration activity monitoring system (RAMOS) [100].…”
Section: Production Of Heterologous Proteins In P Pastorismentioning
confidence: 99%
See 2 more Smart Citations
“…Production of large amounts of heterologous proteins in shake-flask culture is difficult, due to the limitations of volume, oxygen transfer, substrate addition and an inability to monitor these factors efficiently. Methods of monitoring methanol in shake flasks are available, such as organic solvent vapour detectors [40], and the oxygen transfer of these systems can be increased by the use of baffles [114]. On-line measurement of oxygen and carbon dioxide transfer rates in shake flasks has also been demonstrated using a respiration activity monitoring system (RAMOS) [100].…”
Section: Production Of Heterologous Proteins In P Pastorismentioning
confidence: 99%
“…Protein levels in fermenter culture are typically much higher than in shake-flask cultures, although this may be due to poor optimization of methanol-feeding strategies in shake-flask cultures [40]. For this reason, scale-up from shake flask to bioreactor requires much more reoptimization than scale-up from small to large bioreactors [21].…”
Section: Process Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Brierley et al [5] observed that the Mut + strain was very sensitive to changes in the residual methanol level. Guarna et al [41] compared limited growth to growth while maintaining methanol at 0.3% (v/v) in shake flasks. Katakura et al [42] determined the specific growth rates on methanol at several levels.…”
Section: Growth Modelmentioning
confidence: 99%
“…The discrepancy may be ascribed to a high content of calcium (mM grade) and other nutrition components in yeast extract and tryptone (Farrell et al, 1993). For BMMY medium, it may also reflect a suboptimal induction strategy that resulted in carbon source starvation (Guarna et al, 2000).…”
Section: Growth Characteristics Of Pichia Pastoris Pppmr1 and Gs115 Omentioning
confidence: 99%